Questioning Identity Construction and Free Will in Kurt Vonnegut’s Mother Night (1961): A Postmodern Viewing - BOUSSEBIA, Hadjer; BELFERD, Ihssane; MOUISSA ,Fattoum (University of Ammar Theledji -Laghouat, 2021)
The issue of identity construction and the problem of free will have always been a matter of question in postmodern context. Postmodern literature fairly reflects this combination through attempting to interpret both concepts as social constructs. Kurt Vonnegut is among the postmodern authors who are dedicated to portraying the mayhem of identity construction in relation to the endless argument over the authenticity of free will. Vonnegut, through his fiction, depicts the critical journey towards identity formation and the interrogation of free will and fate, mainly in his oeuvre Mother Night. This postmodern novel embodies the protagonist’s struggle with the consequences of his identity falsification during the Second World War. This dissertation, therefore, elucidates the process of identity masquerading and its psychological impact over the psyche of the characters, chiefly the case of the protagonist’s troubled identity. In addition, it investigates the validity of free will and questions the correlation between free will and identity formation. Accordingly, the conducted research is overall based on the psychoanalytical approach to analyse the psychological and sociological factors that subsided the crisis of identity. Additionally, a humanistic approach is applied in order to achieve a comprehensive interpretation of the selected variables. As a result, the final elucidations have revealed that the characters’ troubled identities could be traced back to the instability and unsteadiness that featured the postmodern epoch. Furthermore, the concept of free will is a human construct that is predetermined by a set of psychological external/internal factors.